Nanomaterials and textiles: Review on materials and applications - Boris Mahltig (Journal of Engineered Fibers and Fabrics)
Textile and fiber materials lead in combination with nanomaterials to innovative and functional products of high scientific interest. However, also industrial and consumer products are based on this combination. With this background, the current review presents and categorizes different nanomaterials in respect to their application on textiles. The main goal of the current review paper is to present nanomaterials and its possibilities in combination with textiles for achievement of new and functional materials. For this, several types of materials are presented in detail, as sol-gel coatings, effect pigments, electro spinning and many more. Also, a view on several applications and functionalities is given, as photoactivity, luminescence, antimicrobial properties etc. Altogether a structural paper is supported guiding the reader through this topic concerning those innovative materials.